The Influence of Ground Granulated Blast Furnace Slag (GGBS) as Cement Replacement on the Properties of Sand Cement Brick - Mat Dom, Adek Ainie; Abdul Hamid, Noor Azlina; jamaluddin, Norwati; Othman, Nor Hazurina (International Journal of Sustainable Construction Engineering and Technology, 2022)
Carbon dioxide (CO2) emissions from cement manufacturing contribute significantly to greenhouse gases. However, cement manufacture is necessary since a vast number of bricks are required to satisfy residential housing demand. Considering this crucial environmental impact, cement is encouraged to form futuristic civilizations. Cement replacement is ideally a good proposition to produce green and sustainable sand cement brick to reduce CO2 emissions. This study investigates the influence of Ground Granulated Blast Furnace Slag (GGBS) as a partial cement replacement of sand cement brick. The percentages replacement of GGBS are 0%, 10%, 20%, 30%, 40%, 50% and 60% by mass of the cement with mix design ratio of 1:3 and 0.6 water cement ratio. All the bricks were curing up to 90 days. This research investigates the material characterization of Ordinary Portland Cement (OPC) and GGBS such as specific gravity, particle size distribution and microscopy analysis. The water absorption test and compressive strength of bricks were also carried out for its durability and mechanical properties. The experimental results indicate that the optimum replacement of GGBS in sand cement brick is in range of 10% to 50% which has a potential for application in the masonry production industry.